Efficient synthesis of tetrahydronaphthalene- or isochroman-fused spirooxindoles using tandem reactions. Issue 107 (19th October 2015) - Wang, Biao; Leng, Hai-Jun; Yang, Xue-Yuan; Han, Bo; Rao, Chao-Long; Liu, Li; Peng, Cheng; Huang, Wei
Abstract : The cascade reaction involving a Michael–aldol or vinylogous Henry-acetalization relay is described. We have used the cascade reaction to assemble tetrahydronaphthalene- or isochroman-fused spirooxindoles and other drug-like spirocyclic scaffolds. Abstract : The flexible and simple cascade reaction involving a Michael–aldol or vinylogous Henry-acetalization relay is described. We have used the cascade reaction to assemble functionalized tetrahydronaphthalene- or isochroman-fused spirooxindoles and other drug-like spirocyclic scaffolds. The mild reaction conditions, short reaction times, and high tolerance for various functional groups make this method attractive for constructing pharmacologically interesting architectures.